Water vapor modified chemical capacitance carbon and preparation method and application thereof

By modifying chemical capacitor carbon with water vapor, the pore structure and surface properties of chemical capacitor carbon are changed, giving it the characteristics of physical capacitor carbon. This solves the problem of insufficient performance of supercapacitors in extreme environments and achieves high specific capacity and improved stability.

CN119296979AInactive Publication Date: 2025-01-10BEIJING HCC ENERGY TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411844420.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing supercapacitors perform poorly in extreme environments, especially under high humidity and high temperature conditions, where their capacity decays rapidly and their internal resistance changes rapidly. They cannot pass the double "85" 1000-hour aging test, which limits their application range.

Method used

A method for modifying chemically prepared capacitor carbon using steam involves modifying the capacitor carbon prepared by the chemical method with steam at high temperature, thereby changing its pore structure and surface properties, so that it possesses the characteristics of good conductivity, fast adsorption rate and low agglomeration of physically prepared capacitor carbon.

Benefits of technology

It improves the specific capacitance and electrochemical stability of capacitors, reduces the capacitance decay rate and internal resistance change rate, and enables them to pass high-temperature aging tests, thus expanding the application range of supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119296979A_ABST
    Figure CN119296979A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of water vapor modified chemical capacitance carbon, which comprises the following steps: (1) taking an intermediate of current commercial chemical capacitance carbon, namely activated carbon which is not calcined at a high temperature, as a carbon material, putting the carbon material into a corundum boat, and putting the corundum boat into a tubular furnace; (2) introducing inert gas into the tubular furnace, heating to 250 DEG C at the heating rate of 10-15 DEG C / nim, switching the inert gas into water vapor with the flow of 0.15-0.35 L / min and the constant heating rate, continuously heating to 850-950 DEG C, and keeping the temperature for specified time; and (3) naturally cooling to 750 DEG C, switching to inert gas, continuously cooling to room temperature, and taking out to obtain the modified capacitor carbon. The capacitor carbon modified by the chemical carbon has the properties of the capacitor carbon prepared by a physical method, and the capacitor assembled by the carbon is resistant to high temperature and stable in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitors, and more particularly to a water vapor modified chemical capacitor carbon and a preparation method and application thereof. Background Art

[0002] Supercapacitors have the advantages of high capacity, fast charging and discharging, long life, and environmental friendliness. They are widely used in aerospace, marine vessels, national defense and military industry, transportation, electronic information, and instrumentation. With the advancement of science and technology, their application scope is getting wider and wider. However, supercapacitors currently perform poorly in extreme environments. For example, in high humidity and high temperature conditions, the capacity decays quickly and the internal resistance changes greatly. Due to this shortcoming, they cannot pass the double "85" 1000-hour aging test, which seriously hinders the further use of supercapacitors.

[0003] The key carbon material of supercapacitors is capacitor carbon. The quality of capacitor carbon directly determines the capacity and stability of supercapacitors. There are currently two methods for preparing commercial capacitor carbon, one is chemical method and the other is physical method. The chemical method uses chemicals as activators (mainly potassium hydroxide) and carbon-containing materials as carbon sources, grinds them into powder, mixes the two, activates them at high temperature for a certain period of time, and the activator acts on the carbon material, the carbon material is etched, and then is post-processed to produce porous capacitor carbon. This preparation method has a high activation temperature and a high carbon yield. The prepared capacitor carbon has high methylene blue adsorption capacity and iodine value, large specific surface area, and developed micropores, but has a high organic and inorganic ash content. The initial specific capacitance of the capacitor prepared as an electrode material is high, the capacity decays quickly, the internal resistance change rate is large, and the high-temperature life is short. The physical method uses water vapor or carbon dioxide as an activator (mainly water vapor), and wood materials as a carbon source. The wood materials are crushed into the particle size required by the process, put into an activation furnace, and activated with an activated gas. The carbon reacts with water vapor to generate carbon monoxide and carbon dioxide gas. The gas separates from the carbon body to form pores, and is post-processed to become a commodity physical capacitor carbon. This preparation method has a high activation temperature, a long activation time, and a low carbon yield. The prepared capacitor carbon has low methylene blue adsorption and iodine value, a small specific surface area, but good conductivity, fast dispersibility and adsorption speed, and low organic and inorganic ash content. It is used as an electrode material to prepare a capacitor with low capacity attenuation rate, low internal resistance, and long life. It is stable at high temperature and high pressure. It can withstand the "double 85" 1000-hour aging test. Since the capacitor carbon prepared by the physical water vapor method has low methylene blue adsorption force and iodine value, small specific surface area, and low capacitance when assembled into a capacitor, the YP-50 coconut shell-based capacitor carbon prepared by the physical water vapor method in Japan, when assembled into a button capacitor, has an initial capacitance of 106F / g, while the initial capacitance of commercial petroleum coke-based capacitor carbon currently prepared by chemical method is as high as 142F, and the difference in specific capacitance between the two is 36F. The specific capacitance of Japan's YP-50 coconut shell-based capacitor carbon is the capacitor carbon with the highest specific capacitance among the physical method commercial capacitor carbons on the market. Based on the good conductivity, dispersibility and adsorption speed of the capacitor carbon prepared by the physical method, it can be prepared as an electrode material for a capacitor with low capacitance attenuation rate and long high temperature life. In recent years, carbon material experts at home and abroad have been studying how to improve the specific capacitance of physical method capacitor carbon, but so far, no physical method capacitor carbon has exceeded the specific capacitance of YP-50 coconut shell-based capacitor carbon.

[0004] In order to improve the specific capacity of capacitor carbon prepared by physical method, adapt the performance of capacitors in extreme environments, and further expand the application scope of capacitors, after half a year of experimental research, we invented a method of changing the properties of capacitor carbon prepared by chemical method by using water vapor, so that the capacitor carbon prepared by chemical method can have the characteristics of good conductivity, fast adsorption speed, and low agglomeration of capacitor carbon prepared by physical method. The capacitors made of modified capacitor carbon have the same characteristics as capacitors made of capacitor carbon prepared by physical method, such as low attenuation rate and long high temperature life. Summary of the invention

[0005] In view of this, the present invention provides a method for modifying chemical capacitor carbon with water vapor. The activated carbon prepared by the method has large specific surface area, wide pore radius, good conductivity, fast adsorption speed, low agglomeration, and the same properties as capacitor carbon prepared by physical method. The modified capacitor carbon is used to make capacitor electrodes. The capacitor has high specific capacity, low attenuation rate, long high-temperature life, and can smoothly pass the "double 85" aging test; and the activation time is short and the carbon yield is high.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing water vapor modified chemical capacitor carbon comprises the following steps:

[0008] (1) Take the intermediate of commercial chemical capacitor carbon - uncalcined activated carbon as the base carbon, weigh the base carbon and put it into the corundum boat, with the base carbon attached to the boat wall, leaving a space in the middle of the boat, and the corundum boat is not covered with a lid;

[0009] (2) Place the corundum boat containing the activated carbon that has not been calcined at high temperature in the middle of the tubular furnace, put in the furnace plug, seal it, introduce nitrogen into the tubular furnace, raise the temperature to 250°C at a heating rate of 10-15°C / min, turn off the nitrogen, introduce water vapor at a flow rate of 0.15-0.35 L / min, keep the heating rate unchanged, continue to raise the temperature to 850-950°C, and keep it at this temperature for 30-60 min;

[0010] (3) The temperature is naturally lowered to 750°C, water vapor is replaced with high-purity nitrogen, and the temperature is further lowered to room temperature. The mixture is taken out and mixed to obtain modified chemical capacitor carbon.

[0011] Preferably, the intermediate of the commercial chemical capacitor carbon, the activated carbon that has not been calcined at high temperature, is obtained by activating the carbon material with potassium hydroxide.

[0012] Preferably, the carbon material includes petroleum coke, coconut shell carbonized material, walnut shell, phenolic resin, lignin or asphalt.

[0013] Another object of the present invention is to provide the use of the above-mentioned water vapor modified chemical capacitor carbon in the preparation of capacitors.

[0014] The modified chemical capacitor carbon is mixed with carbon black and 60% PTFE emulsion to prepare slurry, and the carbon slurry is applied to the aluminum foil of the coating machine, formed to obtain a double-sided electrode, dried, rolled and compacted, and the carbon electrode is cut into electrode strips of a certain width by a cutting machine; the carbon electrode strip is placed in a winding core, a casing, and vacuum dried, and 1M Et4NBF4 / AN is used as an electrolyte, and liquid is injected in a glove box with high-purity argon gas, welded, and aged to obtain a 10F columnar capacitor.

[0015] Preferably, the mass ratio of the modified chemical capacitor carbon to carbon black and 60% PTFE emulsion is 8.4:1:0.6

[0016] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0017] (1) The method of water vapor modification of chemical capacitor carbon of the present invention does not add other steps:

[0018] The method of water vapor modification of chemical capacitor carbon of the present invention is basically the same as the method of preparing capacitor carbon by chemical method, except that the last step of the chemical method of preparing capacitor carbon in the box furnace is to pass nitrogen instead of water vapor, and the calcination temperature of ≤800°C is changed to a water vapor modification temperature of 850-950°C. No other steps or equipment are added, and the method is simple.

[0019] (2) The method of water vapor modification of chemical capacitor carbon of the present invention improves working efficiency:

[0020] At present, the activated carbon company produces commercial capacitor carbon by chemical method. The activation time is 4-8 hours from the time the activated material enters the activation furnace to the time the activated material is out of the furnace after being activated. In addition, the water vapor modification takes 4-8 hours, and the total time is 8-16 hours. If water vapor activation is used alone, the total residence time of the activated material in the activation furnace is 60-80 hours, and secondary activation is required. The first activation time of the activated material entering the furnace is 10-20 hours. After it is out of the furnace, it is cooled and then entered into the furnace for the second activation, and the activation time is 50-60 hours. The time used for water vapor modification of chemical capacitor carbon is 64 hours shorter than that used by the physical method. Therefore, the water vapor modification of chemical capacitor carbon has fast activation and high efficiency.

[0021] (3) The method of water vapor modification of chemical capacitor carbon of the present invention increases the carbon yield and reduces the cost:

[0022] At present, the carbon yield of commercial capacitor carbon produced by the chemical method of activated carbon companies is 70%, and the carbon yield of chemical carbon modified by water vapor is 65%, with a total carbon yield of 45.5%. The carbon yield of capacitor carbon prepared by water vapor method using coconut shell particle carbonization material as carbon source is 25%. The total carbon yield of chemical carbon preparation and chemical carbon modified by water vapor is 20.5 percentage points higher than that of capacitor carbon prepared by water vapor method. The carbon yield is increased, which reduces the cost of capacitor carbon.

[0023] (4) The method of modifying chemical capacitor carbon with water vapor of the present invention changes the properties of chemical capacitor carbon and gives it the characteristics of physical capacitor carbon:

[0024] After chemical capacitor carbon was modified by water vapor, the carbon was reactivated at a high temperature of 900 degrees and water vapor, the pore size became wider, the surface functional groups decreased, the viscosity decreased, and the dispersion and adsorption speed increased.

[0025] (5) The method of water vapor modification of chemical capacitor carbon of the present invention is to modify the chemical petroleum coke-based commercial capacitor carbon with water vapor, and the methylene blue adsorption capacity, iodine value, and filling density are 24% higher than the methylene blue adsorption capacity of the Japanese YP-50, which is the highest physical capacitor carbon at present, 23.5% higher than the iodine adsorption value, and 12.5% ​​higher than the methylene blue adsorption capacity of the Japanese YP-50, which is the highest physical capacitor carbon at present. The methylene blue adsorption capacity, iodine value, and filling density of the chemical coconut shell-based commercial capacitor carbon after water vapor modification are 24% higher than the methylene blue adsorption capacity, iodine adsorption value, and filling density of the Japanese YP-50, which is the highest physical capacitor carbon at present, 46.2% higher than the methylene blue adsorption capacity, iodine adsorption value, and filling density of the highest physical capacitor carbon at present. Although the method of water vapor modification of chemical capacitor carbon does not directly improve the methylene blue adsorption capacity, iodine value, and filling density of physical capacitor carbon, it has a method of water vapor modification of chemical capacitor carbon. The capacitor carbon prepared by this method has the same physical properties as the physical capacitor carbon and is of higher quality than the physical capacitor carbon.

[0026] (6) The prepared capacitor carbon and commercial chemical capacitor carbon were assembled into two groups of columnar capacitors of 2.7v10F using the water vapor modified chemical capacitor carbon method of the present invention. The capacitor carbon was subjected to an aging test at 85°C using 1 M EtN4BF4 / AN solution as the electrolyte. In the high temperature aging test, the chemical capacitor carbon had a high initial capacity. As the number of charge and discharge cycles increased and the time prolonged, the internal resistance increased rapidly and the capacity decayed rapidly. After aging for 1000 hours, the internal resistance change rate and capacity decay rate exceeded 300% and 20% respectively. For the capacitor carbon modified by water vapor, the internal resistance change rate and capacity decay rate were less than 300% and 20% respectively. The aging test showed that the capacitor prepared by the modified chemical capacitor carbon had good electrochemical stability in extreme environments and had the same capacity as the commercial chemical capacitor carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0028] Figure 1 The capacitance carbons are assembled into 2.7v10F capacitors, and the internal resistance change rate is measured after 1000h aging at +85℃.

[0029] Figure 2The capacitance carbons of each capacitor are assembled into a 2.7v10F capacitor, and the capacitance change rate after aging for 1000h at a temperature of +85℃;

[0030] Figure 3 The pore size distribution of chemical petroleum coke activated carbon modified by high-temperature steam and calcined by high-temperature nitrogen;

[0031] Figure 4 This is the pore size distribution of capacitor carbon prepared by chemical coconut shell-based activated carbon modified by high-temperature steam and calcined by high-temperature nitrogen. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] The intermediate of commercial capacitor carbon, uncalcined activated carbon, which is currently prepared using petroleum coke as carbon material and potassium hydroxide as activator, is used as base carbon (see Comparative Example 1 for the specific preparation method). Its average particle size D50 is 8um. 40g of this carbon is weighed and evenly loaded into two corundum boats, so that the base carbon is attached to the boat wall, leaving space in the middle of the boat, and the corundum boat is not covered with a lid;

[0035] Place two corundum boats containing carbon in a tube furnace, seal it, introduce nitrogen gas, heat it up to 250℃ at a heating rate of 12℃ / nim, change it to water vapor, the water vapor flow rate is 0.3 L / min, the heating rate remains unchanged, continue to heat it up to 950℃, keep it warm for 50min, cool it down naturally to 750℃, change it to nitrogen, cool it down to room temperature, take it out, and get the modified chemical capacitor carbon. Prepare 350g of modified chemical capacitor carbon according to this step and mix it.

[0036] The adsorption capacity of the modified chemical capacitor carbon was tested with 0.1g of 0.15% methylene blue solution, 31ml, and the iodine value was 2002mg / g. The filling density was 0.45g / ml and the specific surface area was 1917.9m 2 / g, total pore volume 0.9m 3 / g, micropore specific surface area 1695.798m 2 / g, micropore volume 0.71m 3 / g, average pore size 1.879nm, the data are shown in Table 1, the nitrogen, hydrogen, oxygen and carbon contents in the capacitor carbon are analyzed by element analyzer to be 0.26%, 0.36%, 0.31% and 98.82% respectively, the data are shown in Table 2, and the pore size distribution is shown in Figure 3 ;

[0037] According to the above steps, 350 g of modified capacitor carbon was prepared to prepare a 2.7 V 10 F column capacitor;

[0038] (1) Mixing the modified chemical capacitor carbon, acetylene black and 60% PTFE emulsion in a mass ratio of 8.4:1:0.6, adding water into a pulping machine for mixing and pulping;

[0039] (2) The carbon slurry is applied onto the aluminum foil of the coating machine and formed into a double-sided carbon electrode cloth with a width of 500 mm.

[0040] (3) Drying in a vacuum dryer at 80°C;

[0041] (4) Compacting with a roller press to prepare an electrode cloth with a thickness of 230 μm;

[0042] (5) Cutting into electrode strips of a certain width by a cutting machine;

[0043] (6) Placing the carbon electrode strip on the winding core of the winding machine;

[0044] (7) Using 1 M Et4NBF4 / AN as the electrolyte, in a glove box filled with high-purity argon, inject the electrolyte into the electrode core, put it into the shell, and package it;

[0045] (8) After vacuum drying, welding, aging and other steps, a columnar capacitor is obtained.

[0046] The supercapacitor prepared by the modified capacitor carbon was subjected to a high temperature 85°C 1000h aging test, and its termination data were: capacity 8.28F, capacity change rate 18.8%, internal resistance 118.5Ω, internal resistance change rate 248.4%, see Table 3 and Figure 1 , Figure 2 .

[0047] Example 2

[0048] The intermediate of commercial capacitor carbon, uncalcined activated carbon, which is currently prepared using coconut shell as carbon material and potassium hydroxide as activator, is used as base carbon (see Comparative Example 2 for the specific preparation method). 40g of this carbon is weighed and evenly loaded into two corundum boats, so that the base carbon is attached to the boat wall, leaving space in the middle of the boat, and the corundum boat is not covered with a lid;

[0049] Place two corundum boats containing carbon in a tubular furnace, seal it, introduce nitrogen gas, heat it up to 250°C at a heating rate of 10°C / min, switch to water vapor with a water vapor flow rate of 0.35 L / min, keep the heating rate unchanged, continue to heat it to 900°C, keep it warm for 40 minutes, naturally cool it to 750°C, switch to nitrogen, cool it to room temperature, take it out, and obtain modified chemical capacitor carbon. Prepare 350g of modified chemical capacitor carbon according to this step.

[0050] 350g of the carbon was mixed and tested for methylene blue adsorption capacity of 31ml, iodine value 2312mg / g. Packing density 0.43g / ml, specific surface area 2142m 2 / g, total pore volume 0.9779m 3 / g, micropore specific surface area 1916.85m 2 / g, micropore volume 0.789m 3 / g, average pore size 1.825nm, the data are shown in Table 1, and the nitrogen, hydrogen, oxygen and carbon contents in the capacitor carbon are analyzed by element analyzer to be 0.28%, 0.4%, 0.28% and 98.84% respectively, the data are shown in Table 2;

[0051] According to the method for preparing capacitors in Example 1, the modified chemical capacitor carbon in this example was prepared into a 2.7v10F column capacitor, and an aging test was carried out at a high temperature of 85°C for 1000h. The termination data were: capacitance 8.24F, capacitance change rate 18.4%; internal resistance 106Ω, internal resistance change rate 224.5%. The data are shown in Table 3 and Figure 1 . Figure 2 .

[0052] Comparative Example 1

[0053] In Example 1, the current production process of a company for preparing commercial capacitor carbon from petroleum coke by chemical method is:

[0054] (1) Use petroleum coke as carbon material, grind it into powder, and use potassium hydroxide as activator;

[0055] (2) Material ratio: 1:2;

[0056] (3) Dehydration: Pour petroleum coke powder and potassium hydroxide into the reactor respectively, heat and melt, stir, dehydrate and degas, solidify at 400°C, cool slightly, and put into the activation tank;

[0057] (4) Activation: Place the activation tank into the activation furnace, turn on the power, increase the temperature, pass nitrogen gas, heat to 780°C for 50 minutes, keep warm for 4 hours, cool to 400°C, stop nitrogen gas, take the tank out of the furnace immediately, and sprinkle water;

[0058] (5) Post-treatment: alkali recovery, hydrochloric acid boiling, pickling, water washing to pH 6, and drying to obtain uncalcined capacitor carbon;

[0059] (6) Test: Methylene blue adsorption capacity 36ml, iodine adsorption value 2478mg / g, density 0.44g / ml, specific surface area 2052m 2 / g, total pore volume 0.89m 3 / g, micropore specific surface area 1891.78m 2 / g, micropore volume 0.75m 3 / g, average pore size 1.742nm, the data are shown in Table 1;

[0060] (7) Calcination: Put the dry carbon into a graphite can and place it in a calcination furnace. Turn on the power, increase the temperature, pass nitrogen gas, heat to 760°C for 50 minutes, keep the temperature for 2 hours, cool to room temperature, stop nitrogen gas, and take the carbon out of the furnace.

[0061] (8) Pour into a mixer, introduce nitrogen, turn on the power, rotate, mix at 60r / nim speed for 30min, take samples for testing, suck out the carbon powder into a bag, and obtain commercial capacitor carbon;

[0062] (9) Test: Methylene blue adsorption capacity 33ml, iodine adsorption value 2016mg / g, density 0.46g / ml, specific surface area 1952.24m 2 / g, pore volume 0.804m 3 / g, micropore specific surface area 1822.375m 2 / g, micropore volume 0.726m 3 / g, average pore size 1.722nm, data are shown in Table 1, and the nitrogen, hydrogen, oxygen and carbon contents in the chemical capacitor carbon are analyzed by element analyzer, which are 0.63%, 0.27%, 0.33% and 98.3% respectively, and the data are shown in Table 2. The pore size distribution is shown in Figure 3 .

[0063] Take 350g of this commercial capacitor carbon and prepare it into a 2.7v10F column capacitor according to the method for preparing a capacitor in Example 1. Its capacitance is 8.62F, and the capacitance change rate is 28.7%; its internal resistance is 164.5Ω, and the internal resistance change rate is 310.3%. The data are shown in Table 3 and Figure 1 , Figure 2 .

[0064] Comparative Example 2

[0065] In Example 2, the current chemical process for preparing coconut shell-based commercial capacitor carbon by a certain company is:

[0066] (1) Use coconut shell carbonized material as carbon material, grind it into powder, and use potassium hydroxide as activator;

[0067] (2) Material ratio: 1:1.9;

[0068] (3) Dehydration: Pour coconut shell carbonized powder and potassium hydroxide into the reaction kettle respectively, heat to melt, stir, dehydrate and degas, solidify at 400℃, cool slightly, and put into the activation tank;

[0069] (4) Activation: Place the activation tank into the activation furnace, turn on the power, increase the temperature, pass nitrogen gas, heat to 780°C for 50 minutes, keep warm for 4 hours, cool to 400°C, stop nitrogen gas, take the tank out of the furnace immediately, and sprinkle water;

[0070] (5) Post-treatment: alkali recovery, hydrochloric acid boiling, pickling, water washing to pH 6, and drying to obtain uncalcined capacitor carbon;

[0071] (6) Test: Methylene blue adsorption capacity 32.5ml, iodine adsorption value 2010mg / g, density 0.46g / ml, specific surface area 1866.268m 2 / g, total pore volume 0.8116m 3 / g, micropore specific surface area 1731.84m 2 / g, micropore volume 0.692m 3 / g, average pore size 1.74nm, its data are shown in Table 1;

[0072] (7) Calcination: Put the ground carbon into a graphite can and place it in a calcining furnace. Turn on the power, increase the temperature, pass nitrogen gas, heat to 760°C for 50 minutes, keep the temperature for 2 hours, cool down to room temperature, stop nitrogen gas, and take it out of the furnace immediately.

[0073] (8) Pour into the mixer, introduce nitrogen, turn on the power, rotate, mix at 60r / nim speed for 30min, take samples for testing, suck out the carbon powder into the bag, evacuate the air, and obtain commercial capacitor carbon;

[0074] (9) Test: Methylene blue adsorption capacity 31ml, iodine adsorption value 2294mg / g, density 0.49g / ml, specific surface area 1931.338m2 / g, total pore volume 0.8425m 3 / g, micropore specific surface area 1801.861m 2 / g, micropore volume 0.724m 3 / g, average pore size 1.745nm, the data are shown in Table 1;

[0075] The nitrogen, hydrogen, oxygen and carbon contents in the commercial capacitor carbon were analyzed by element analyzer, and the results were 0.54%, 0.19%, 0.3% and 98.64% respectively. The data are shown in Table 2. The pore size distribution of the activated carbon is shown in Figure 4 ;

[0076] Take 350g of this commercial capacitor carbon and prepare it into a 2.7v10F column capacitor according to the method for preparing a capacitor in Example 1. Its capacitance is 7.48F, and the capacitance change rate is 25.9%; its internal resistance is 159.7Ω, and the internal resistance change rate is 305.4%. The data are shown in Table 3 and Figure 1 , Figure 2 .

[0077] Comparative Example 3

[0078] Take Japanese YP-50 water vapor physical method capacitor carbon

[0079] The test results show that the methylene blue adsorption capacity is 25ml, the iodine adsorption value is 1621mg / g, the density is 0.4g / ml, and the specific surface area is 1586m 2 / g, average pore diameter 1.87nm, pore volume 0.741m 3 / g, and its test data are shown in Table 1;

[0080] Take 350g of YP-50 capacitor carbon and prepare it into a 2.7v10F column capacitor according to the method for preparing capacitors in Example 1. The capacitance is 6.63F, the capacitance change rate is 18.2%; the internal resistance is 99Ω, and the internal resistance change rate is 223.6%. The data are shown in Table 3:

[0081] Table 1 Physical data of capacitor carbon prepared under different conditions

[0082] name Methylene blue adsorption (ml) Iodine value (mg / g) Density(g / ml) <![CDATA[Total pore area (m 2 / g)]]> <![CDATA[Total pore volume (m 3 / g)]]> <![CDATA[Micropore area (m 2 / g)]]> <![CDATA[Micropore volume (m 3 / g]]> Average pore size (nm) Example 1 31 2002 0.45 1917.9 0.9 1695.798 0.71 1.879 Example 2 31 2312 0.43 2142.848 0.9779 1916.85 0.789 1.825 Comparative Example 1 33 2016 0.46 1952.24 0.804 1822.375 0.726 1.722 Comparative Example 2 31 2294 0.49 1931.338 0.8425 1801.861 0.724 1.745 Comparative Example YP-50 Carbon 25 1621 0.4 1586 0.741 1.87 Petroleum coke uncalcined charcoal 36 2478 0.44 2052.2 0.89 1891.78 0.75 1.742 Uncalcined coconut shell charcoal 32.5 2010 0.46 1866.268 0.8116 1731.84 0.692 1.74

[0083] In Table 1, the chemical petroleum coke-based activated carbon of Example 1 and Comparative Example 1 are compared in terms of methylene blue adsorption, iodine value, and specific surface area of ​​the capacitor carbon obtained by high-temperature steam modification and high-temperature nitrogen calcination, respectively. The methylene blue adsorption, iodine value, and specific surface area of ​​the capacitor carbon obtained by high-temperature steam modification are slightly lower, while the average pore size and pore volume are slightly higher than those of the capacitor carbon obtained by high-temperature nitrogen calcination;

[0084] The chemical coconut shell-based activated carbons of Example 2 and Comparative Example 2, respectively, have the same methylene blue adsorption capacity when modified by high-temperature steam and calcined by high-temperature nitrogen, while the surface area, iodine value, average pore size, and pore volume of the capacitor carbons modified by high-temperature steam are higher than those calcined by high-temperature nitrogen.

[0085] Whether chemical petroleum coke-based activated carbon or chemical coconut shell-based activated carbon modified by high-temperature steam, the methylene blue adsorption capacity, iodine value, specific surface area, pore size and pore volume of the capacitor carbon are much higher than those of YP-50 coconut shell-based steam physical carbon.

[0086] The increase in pore size and pore volume speeds up the adsorption rate of capacitor carbon, improves the conductivity and the speed of ions entering and exiting the liquid, and increases the stability of the capacitor: the increase in methylene blue adsorption capacity, iodine value, and specific surface area will increase the specific capacitance.

[0087] Table 2 Data on nitrogen, hydrogen, oxygen and carbon content in various capacitor carbons

[0088] name nitrogen hydrogen oxygen carbon Example 1 0.26 0.36 0.31 98.82 Example 2 0.28 0.4 0.28 98.84 Comparative Example 1 0.63 0.27 0.33 98.3 Comparative Example 2 0.54 0.19 0.3 98.64

[0089] Table 2 The data of nitrogen, hydrogen, oxygen and carbon content in each capacitor carbon show that the nitrogen and oxygen contents in the embodiments are lower than those in the comparative examples, respectively, while the carbon content in the embodiments is higher than that in the comparative examples. The lower the nitrogen and oxygen contents in the capacitor carbon, the higher the carbon content, and the smaller the change rate of the internal resistance and capacity of the assembled capacitor.

[0090] Table 3 Data of aging test of 2.7V 10F capacitors assembled from various capacitor carbons at +85℃ for 1000h

[0091]

[0092] In Table 3, the capacity change rate and internal resistance change rate of the capacitors assembled from the chemical activated carbon modified by water vapor in Example 1-2 and the Japanese YP-50 physical capacitor carbon were lower than 20% and 300%, respectively, and passed the high temperature +85°C 1000h aging test; while the capacity change rate and internal resistance change rate of the commercial chemical activated carbon in Comparative Example 1-2 were higher than 20% and 300%, respectively, and failed the high temperature +85°C 1000h aging test. The aging experiment shows that the properties of the chemical carbon are changed by high temperature water vapor activation, and the chemical carbon is given the properties of physical carbon.

[0093] Moreover, the specific capacitance of the modified capacitor carbon is 20% higher than that of Japanese YP-50 physical capacitor carbon, slightly lower than that of petroleum coke-based chemical capacitor carbon, and 9.7% higher than that of coconut shell-based chemical capacitor carbon. This solves the problem of low capacitance of capacitors assembled from physical capacitor carbon, and also solves the problem of fast capacitance decay and short life of capacitors assembled from chemical capacitor carbon in extreme high temperature environments, thus expanding the application range of double-layer capacitors.

[0094] In the embodiment and comparative example of Table 3, activated carbon prepared from petroleum coke and coconut shell as carbon materials is subjected to water vapor modification of capacitor carbon. The modified capacitor carbon has the characteristics of physical capacitor carbon, and the stability of the modified capacitor carbon being assembled into capacitors is greatly improved. Water vapor modification is not limited to activated carbon prepared from petroleum coke and coconut shell as carbon materials, and this method is also applicable to water vapor modification of chemical activated carbon prepared from other carbon materials. The present applicant uses this method to prepare activated carbon from lignin, asphalt, and thermosetting phenolic resin as carbon materials, and the capacitor carbon after water vapor modification is assembled into capacitors. Its electrochemical properties are the same as the electrochemical properties of capacitor carbon assembled from activated carbon prepared from petroleum coke and coconut shell as carbon materials.

[0095] Depend on Figure 3 ,Depend on Figure 4It can be seen that the pore size distribution curve peaks of petroleum coke, coconut shell charcoal prepared by chemical method and charcoal calcined under nitrogen protection at 760℃ are mostly around 1nm, with more micropores. The pore size curve of capacitor carbon modified by high-temperature water vapor shifts to the right, moving in the direction of increasing pore size. The micropores of the original carbon (petroleum coke and coconut shell charcoal prepared by chemical method) have been widened, the pore radius has increased, and the average pore size has increased from <1.75nm to >1.8nm. The wider pore size is beneficial to the transfer of charge, the conductivity is improved, the internal resistance is reduced, the pore structure of activated carbon is improved, the stability of the capacitor is improved, and the life of the capacitor is extended.

[0096] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0097] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing water vapor modified chemical capacitor carbon, characterized in that: The following steps are involved: (1) Take the intermediate of commercial chemical capacitor carbon - uncalcined activated carbon as the base carbon, weigh the base carbon and put it into the corundum boat, with the base carbon attached to the boat wall, leaving a space in the middle of the boat, and the corundum boat is not covered with a lid; (2) Place the corundum boat containing the activated carbon that has not been calcined at high temperature in the middle of the tubular furnace, put in the furnace plug, seal it, introduce nitrogen into the tubular furnace, raise the temperature to 250°C at a heating rate of 10-15°C / min, turn off the nitrogen, introduce water vapor at a flow rate of 0.15-0.35 L / min, keep the heating rate unchanged, continue to raise the temperature to 850-950°C, and keep it at this temperature for 30-60 min; (3) The temperature is naturally lowered to 750°C, water vapor is replaced with high-purity nitrogen, and the temperature is further lowered to room temperature. The mixture is taken out and mixed to obtain modified chemical capacitor carbon.

2. The method for preparing a water vapor modified chemical capacitor carbon according to claim 1, characterized in that: The intermediate of the commercial chemical capacitor carbon, the activated carbon that has not been calcined at high temperature, is obtained by activating the carbon material with potassium hydroxide.

3. The method for preparing a water vapor modified chemical capacitor carbon according to claim 2, characterized in that: The carbon material includes petroleum coke, coconut shell carbonized material, walnut shell, phenolic resin, lignin or asphalt.

4. A water vapor modified chemical capacitor carbon, characterized in that: The carbon is prepared by the method for preparing the water vapor modified chemical capacitor carbon according to any one of claims 1 to 3.

5. Use of the water vapor modified chemical capacitor carbon as claimed in claim 4 in the preparation of capacitors.

6. The use of the steam-modified chemical capacitor carbon in the preparation of capacitors according to claim 5, characterized in that: The modified chemical capacitor carbon is mixed with carbon black and 60% PTFE emulsion to prepare slurry, and the carbon slurry is applied to the aluminum foil of the coating machine to form a double-sided electrode, which is then dried and rolled to be compacted. The carbon electrode is cut into electrode strips of a certain width by a cutting machine; the carbon electrode strip is placed in a winding core, a casing, and vacuum dried. 1M Et4NBF4 / AN is used as an electrolyte, and the electrolyte is injected in a glove box of high-purity argon gas, welded, and aged to obtain a 10F columnar capacitor.

7. The use of a water vapor modified chemical capacitor carbon in the preparation of a capacitor according to claim 6, characterized in that: The mass ratio of the modified chemical capacitor carbon to carbon black and 60% PTFE emulsion is 8.4:1:0.6.

Citation Information

Patent Citations

  • 3D network pore structure super-capacitor carbon and preparation method thereof

    CN105645410A

  • Compound nutshell-based activated carbon and preparation method and application thereof

    CN106082210A

  • Potassium carbonate recycling technology

    CN109626399A

  • Device for preparing super-capacitor activated carbon by alkali activation method and preparation method thereof

    CN111232979A

  • Composite petroleum coke-based activated carbon and preparation method therefor, and supercapacitor

    WO2017219943A1